MODEL DATA LOGGER UNTUK MENGUKUR ARUS, TEGANGAN, DAN DAYA PADA SIMULASI PEMBANGKIT LISTRIK TENAGA ANGIN DAN SURYA MENGGUNAKAN ANDROID: Abdurrasyid; Diko Suprayogi - Jurnal, Redaksi Tim (PETIR, 2018)
Monitoring System data at a power plant is the most important part in controlling and supervising a power plant. But in fact its technology monitoring system is still a lot of weakness. This thesis aims to innovate in reading current, voltage, and power at power plants by creating a data logger models that utilize the Arduino microcontroller. Current and voltage will be read by the ACS712 current sensor, then the value of current and voltage will be processed by the Arduino to be changed from analog data into digital data. Once the data is processed and the data will be sent to the Web Server as a database via GPRS Module by utilizing the internet signal. Applications designed on this system using a mobile based application programming android. Application as a user interface making it easier to monitor the generation of data in realtime via android smartphone. Then the data will be processed by the application so that it can be used to view history data readout and print reports. So later this monitoring system will be used to check power at a power plant using only virtual android smartphone and can be accessed anywhere.